1998
DOI: 10.1007/s004649900636
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of benzalkonium chloride chemoneurolytic proximal gastric vagotomy

Abstract: These efficacy studies have demonstrated BAC's potential utility in the performance of endoscopic transmucosal chemoneurolytic PGV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…In that study, the repeated application of this BAK-containing nanoemulsion, twice daily for 2 weeks onto rabbit nostrils indicated safety with no irritation. In fact, this chemical compound is widely used as a disinfectant against bacteria, viruses, pathogenic fungi and mycobacteria, and it has been approved by the Food and Drug Administration as a skin disinfectant [36].…”
Section: Introductionmentioning
confidence: 99%
“…In that study, the repeated application of this BAK-containing nanoemulsion, twice daily for 2 weeks onto rabbit nostrils indicated safety with no irritation. In fact, this chemical compound is widely used as a disinfectant against bacteria, viruses, pathogenic fungi and mycobacteria, and it has been approved by the Food and Drug Administration as a skin disinfectant [36].…”
Section: Introductionmentioning
confidence: 99%
“…25 In gastroenterology, the chemoneurolytic effect of BAC is used for experimental models of vagotomy. 29 The lack of correlation between the density of corneal nerves and corneal sensation might result from this anesthetic effect of antiglaucoma eyedrops in this group of patients. Unfortunately, considering the sample size of our study we could not differentiate between patients receiving preserved and unpreserved eyedrops or different molecules.…”
Section: 21mentioning
confidence: 99%
“…In the stomach, the BAC-denervation procedure has been proposed as a new method to perform parietal cell vagotomy in substitution of the traditional operative procedure, which is an accepted therapy for peptic ulcers that are refractory to medical management [67]. Furthermore, a comparative study of efficacy of several techniques in regard to long-term effects on acid secretion, ulcer prophylaxis, and permanent vagal denervation in a rat model has shown that the BAC chemoneurolytic and laser methods were most effective for decreasing the size of acid-secreting areas [68, 69].…”
Section: New Research Directions and The Potential Use Of Myenterimentioning
confidence: 99%